1993
DOI: 10.1590/s0036-46651993000400005
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis mansoni in an area of low transmission: II. Risk factors for infection

Abstract: Risk factors for Schistosoma mansoni infection were identified using a 1:1 matched case-control design. The work was conducted in the municipality of Pedro de Toledo, São Paulo State, Brazil, an area where the snail host is Biomphalaria tenagophila. Information on water contact patterns, knowledge, attitudes and pratices (kap), socioeconomic and sanitary conditions were obtained by mean of questionnaires. The crude odds ratio estimates and the adjusted odds ratio estimates using the logistic regression model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The current study was consistent with studies conducted in Gondar and Babile [ 12 , 13 ], where there was significant association between intestinal parasitic infections and hand washing practice. A study conducted in Brazil reported that daily contact of open water source results in higher rate of infection by S. mansoni [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was consistent with studies conducted in Gondar and Babile [ 12 , 13 ], where there was significant association between intestinal parasitic infections and hand washing practice. A study conducted in Brazil reported that daily contact of open water source results in higher rate of infection by S. mansoni [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As atividades de controle vêm sendo desenvolvidas nas seguintes regiões do estado: Vale do Rio Paraíba do Sul, vale do Rio Ribeira de Iguape, Baixada Santista, litoral Sul, Vale do Paranapanema e áreas metropolitanas de São Paulo e Campinas. De todas essas regiões, a área dos municípios de Pedro de Toledo e Itariri, no vale do Ribeira, vêm sendo uma das mais ativamente pesquisadas e controladas 6,7,24,25 . O controle da esquistossomose em Pedro de Toledo foi iniciado em 1968 pela Campanha de Combate à Esquistossomose da Secretaria de Saúde do Estado de São Paulo, tendo a Superintendência de Controle de Endemias-SUCEN dado continuidade a partir de 1976.…”
Section: Introductionunclassified